Pengaruh CR, ROE, dan NPM Terhadap Perubahan Laba Pada PT Timah (Persero) Tbk Tahun 2006-2010 - Hanafi Hanafi; Iing Lukman; Lestari Wuryanti (Universitas Malahayati, 2014)
Financial ratio analysis is basically because they want to know the level of profitability (profit) and the level of risk or the soundness of a company. Using comparable reports, including datatentang changes that occur in the amount of rupiah, as well as the percentage of the trend, analysts realize that the ratio of individual will assist in analyzing and interpreting the financial position of a company. The ratio describes a relationship or balance (mathematical relationship) between a certain amount by the number of others, and using the analyzer in the form of this ratio will be able to explain or give an overview to the analyzer about the good or bad things are or the financial position of a company, especially if the ratio of the compared to the comparative ratio is used as a standard Partial assay results variable X, (CR), variables X2 (NPM), X3 (ROE) has thitung> ttable Thus, for the three independent variables that exist Ho rejected and Ha accepted this means masng-masng independent variables partially have influence significant changes in earnings. Results are Simulatan Hypothesis Testing (Test F), shows that the value of F count> F table. Thus rejected Ha Ho accepted This means that there are significant effect between current ratio (CR / X1 (CR), variables X2 (NPM), X3 (ROE) simultaneously or with -Same to changes in income. The coefficient of determination (R2) pad the bottom line measure of how far the ability of the model to explain variations in the dependent variable. The coefficient of determination (R2) obtained 0.995, meaning that 99.5% profit change diperngaruhi pleb variable CR, NPM, and the remaining 0.05% are caused by other factors not included in the equation.